Local Adaption and Meaning Creation in Performance Appraisal - Morten Rossing (Copenhagen Business School (CBS), 2013)
A thorough literature review shows how it is well established in the literature that performance appraisal (PA) in modern organisations is infused with many problems. However, at the same time PA is one of the most institutionalised features of running large corporations everywhere in the Western world. Problems in PA challenges managers and employees and provoke important local adaption and meaning creation processes across workforces in order to allow a meaningful fit between the practice of PA and the task at hand in each workforce. Through 34 qualitative interviews with manager-employee dyads, the study design included a comparative study of local adaption and meaning creation in PA across four different workforces over a full one-year PA-cycle in a case organisation where a one-size-fits-all PA scheme had been implemented. Important differences in environmental dynamics and in manager and employee enactment patterns were found. Understanding these patterns is not only important for our understanding of how PA schemes affect individuals' and organisations' performance. It is also more fundamentally important to our understanding of the dynamics of the problems in PA which have been uncovered, analysed and attempted to be solved over the last 20 years' scholarly research into PA, without any real breakthrough. Austin's (1996) separation between management by delegation versus management by measurement was used as a typology of differences in the task at hand in Sales, R&D, Production and Staffs in the case organisation. Although PA as such is clearly designed to operate within the management by measurement paradigm, comparative findings across workforces show that important differences are present. Particularly, Sales and R&D form contrasting cases in terms of characteristics of the task at hand and characteristics of PA adaption and meaning creation. Thus, the study shows how a standard corporate PA scheme can be twisted in different directions in different workforces to such an extent that in R&D it can even be argued that the scheme in some ways has more similarities with management by delegation than with management by measurement. The study discusses the implications of this and guidance to future research is provided.
hdl:10398/8761
Keywords: 650